Pengembangan Media Pembelajaran Interaktif Berbasis Articulate Storyline pada Pembelajaran Matematika Materi Sistem Persamaan Linear Dua Variabel (SPLDV) Kelas VIII SMP - Somba, Genefif Tavania Meyni; Maukar, Marvel Grace; Sulistyaningsih, Murni (Universitas Cokroaminoto Palopo, 2024)
This research was motivated by students' lack of understanding of basic concepts in SPLDV material, this was caused by various factors, one of which was the lack of use of learning media such as Articulate Storyline which was able to attract students' interest in learning. This causes students to become bored and the learning process becomes less effective. This can be seen from the learning outcomes of students who have not yet reached the KKM of 67.5%. This research aims to develop interactive learning media based on Articulate Storyline in mathematics learning material on systems of linear equations in two variables (SPLDV) for Class VIII SMP to determine the level of validity and effectiveness of the learning media developed. This research method is a type of R&D (Research and Development) research using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Data collection techniques are carried out by observation, interviews and tests. The data collection instrument used was a validation sheet. This research was conducted on 28 students in class VIII_E of SMP Negeri 1 Kawangkoan. The data analysis techniques used are descriptive qualitative and descriptive statistics. From the research results, validity results were obtained for media experts (85%) in the very appropriate category, material experts (100%) in the very appropriate category and effectiveness (86%) in the very effective category.